Osteoporosis diagnosis and ingredients of prescription medications: a population-based study - Huang, Xiaohong; Feng, Zhendong; Li, Xiaohua; Zhu, Dongxu; Zhang, Yingze (Frontiers in Pharmacology, 2025)
BackgroundOsteoporosis (OP) is common in the elderly, who typically have multiple comorbidities. Current guidelines for managing drug-induced OP are limited due to the complexity of multi-agent medications and the lack of sufficient clinical data.MethodsInformation of demographics, health status, prescription medication use, OP diagnoses, and bone fracture history in US adults aged ≥50 years was from NHANES. Administration of individual medication ingredients was extracted and association between medication component use and OP diagnosis was determined. National trends in OP diagnosis, prescription medication use, and medication ingredient administrations were examined.ResultsOP diagnosis prevalence rose from 9.00% to 13.23% during 1999–March 2020 (p-trend = 0.00). Increased medication prescription was noted in OP patients (p-trendNo. prescription medications=4–7 <0.0001, p-trendNo. prescription medications≥8 < 0.0001, and p-trendDays taking medications≥500 < 0.0001). Thirty-four medication ingredients were correlated with OP diagnosis, including three OP-specific medications, three avoided in OP patients in current practice, seven contribute to OP but commonly prescribed, four relieved OP when treating diseases causing secondary OP, two bone health-friendly agents, and 15 lack of prior statistical records to support their clinical use in OP. Amongst 10 ingredients associated with OP diagnosis may be underlying their roles in regulating bone remodeling, sympathetic activity, and gastric acidity, whereas the remaining five were not clear.ConclusionThe findings of this study contribute to updating and improving the existing guidelines. Efforts are recommended to examine how the use of medications contribute to OP and to identify alternative treatments for comorbidities.